Using the Revised Bloom Taxonomy to Analyze Psychotherapeutic Games - Priscilla Haring; Harald Warmelink; Marilla Valente; Christian Roth (International Journal of Computer Games Technology)
Most of the scientific literature on computer games aimed at offering or aiding in psychotherapy provides little information on the relationship between the game’s design and the player’s cognitive processes. This article investigates the use of Bloom’s taxonomy in describing a psychotherapeutic game in terms of knowledge level and cognitive processing. It introduces the Revised Bloom Taxonomy and applies this to five psychotherapeutic games (Personal Investigator, Treasure Hunt, Ricky and the Spider, Moodbot, and SuperBetter) in a two-round procedure. In the first round consensus was reached on the Player Actions with Learning Objectives (PALOs) in each game. The second round sought to determine what level of knowledge and cognitive processing can be attributed to the PALOs by placing them in the taxonomy. Our low intercoder reliability in the second round indicates that Bloom’s Revised Taxonomy is not suitable to compare and contrast content between games.